2023
DOI: 10.1177/16878132231189373
|View full text |Cite
|
Sign up to set email alerts
|

Peristaltic pumping of ternary hybrid nanofluid between two sinusoidally deforming curved tubes

Abstract: This paper aims to inspect the mixed convective peristaltic transport of ternary hybrid nanofluids between two sinusoidally deforming lubricated curved concentric tubes. Titanium, Alumina, and copper nanoparticles are taken for the current problem with blood as a base fluid. The heat equation is also modeled in the presence of heat generation/absorption. The curved shape structure of flow geometry from the external side with a flexible complex nature of the peristaltic endoscope present inside that is similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The numerical values of thermophysical features of nanomaterials and base fluid blood are shown in Table 1. The correlations explaining the thermophysical attributes of trihybrid nanofluids, such as the effective density r thnf , the effective density m thnf , coefficient of thermal expansion rb t ð Þ thnf , effective heat capacity rC p À Á thnf , and thermal conductivity k thnf are respectively stated as 19 :…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical values of thermophysical features of nanomaterials and base fluid blood are shown in Table 1. The correlations explaining the thermophysical attributes of trihybrid nanofluids, such as the effective density r thnf , the effective density m thnf , coefficient of thermal expansion rb t ð Þ thnf , effective heat capacity rC p À Á thnf , and thermal conductivity k thnf are respectively stated as 19 :…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Manjunatha et al 18 inspected the mathematical investigation of electrical conducting heat phenomena in tri nanofluid flowing past a stretching sheet. Recently, Abbas et al 19 reported the mixed convective peristaltic transport of ternary hybrid nanofluids between two sinusoidally deforming lubricated curved concentric tubes. Some important studies regarding nanofluid flow over various geometries can be seen through Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The peristaltic flow of an incompressible Bingham plastic fluid in a curved duct was investigated by Adnan [37]. Trinary hybrid nanofluid flow was investigated by Z. Abbas et al between two sinusoidally deflected curved tubes [38]. The impacts of a magnetic field on the peristaltic movement of Bingham fluid were examined in a study by Adnan [39].…”
Section: Introductionmentioning
confidence: 99%